Modified polyamide particles as well as preparation method and application thereof

By generating zirconia on glass fibers and grafting silane coupling agent, combining syringaldehyde modification and reacting with styrene-maleic anhydride copolymer, the problem of interlayer debonding of polyamide heat insulation strips is solved, significantly Improve the mechanical strength and compatibility of modified polyamide particles and improve the thermal insulation performance.

CN119490743AInactive Publication Date: 2025-02-21江门市融泰新材料科技有限公司

Patent Information

Application Number
CN202411639843.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing polyamide heat insulation strips are prone to interlayer debonding during use, resulting in degradation of thermal insulation performance and deformation of the glue strips.

Method used

The interface binding force between the composite filler and the polyamide is increased by grafting more silane coupling agents on the glass fibers and grafting more silane coupling agents on the composite filler and polyamide. At the same time, the surface of the composite filler is modified using syringaldehyde to improve compatibility with the polyamide system, and react with the anhydride in the styrene-maleic anhydride copolymer to enhance the mechanical strength.

Benefits of technology

The mechanical strength of the modified polyamide particles and compatibility with the polyamide system are improved, the occurrence of interlayer debonding is reduced, and the stability and thermal insulation performance of the heat insulation strip are improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to modified polyamide particles as well as a preparation method and application thereof, and belongs to the technical field of polyamide particles. The modified polyamide particle comprises the following components: polyamide resin, a modified composite filler, a compatibilizer, an antioxidant and a lubricant. The preparation method comprises the following steps: banburying and mixing the polyamide resin, the compatibilizer, the antioxidant and the lubricant, adding the mixture into a double-screw extruder from a main feeding port, adding the modified composite filler from a side feeding port, and carrying out melt extrusion, cooling and pelletizing to obtain the modified polyamide particles. Zirconium oxide is generated on glass fibers, more silane coupling agents are grafted in combination with a tetramethylammonium hydroxide and ethidene diamine compound catalyst, the interface bonding force between the composite filler and polyamide is increased, the surface of the composite filler is modified through syringaldehyde, the compatibility with a polyamide system is increased, and meanwhile, the composite filler can be used for preparing the composite filler. The modified polyamide particles can react with acid anhydride in a styrene-maleic anhydride copolymer, and the mechanical strength of the modified polyamide particles can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyamide particles, and relates to modified polyamide particles and a preparation method and application thereof. Background Art

[0002] As a non-metallic connector that connects the inner and outer aluminum alloy profiles in the current aluminum alloy heat-insulating energy-saving doors and windows, polyamide insulation strips have the function of sealing and blocking water and gas penetration. The quality of the insulation strips directly affects the quality of aluminum building windows. It not only plays an important mechanical role in the heat-insulating aluminum alloy doors and windows, but also has the function of blocking the heat transfer of aluminum alloy door and window frames. The insulation strip is mainly composed of polyamide 66 resin, other resins and glass fiber modified materials. Doors and windows using this type of insulation strip have a low heat transfer coefficient and good heat insulation, sound insulation and dustproof performance.

[0003] For example, the patent document with publication number CN109929243A discloses a heat-resistant polyamide reinforced material with low water absorption and a preparation method thereof, which specifically relates to the field of polymer material technology. The heat-resistant polyamide reinforced material includes the following components: PPA, PA66, glass flakes, glass fibers, antioxidants, and lubricants; the PPA is a copolymer of polyterephthalic acid, polyisophthalic acid, and hexamethylenediamine; wherein the glass fibers and glass flakes serve as reinforcements, and the resin has the function of uniformly dispersing the load, and the interface layer transfers the load to the glass flakes and glass fibers, so that they bear shear loads and compression loads. The glass fibers are short and broken, resulting in a reduction in the bonding force between them and the resin. The glass flakes and glass fibers peel off from the resin matrix, and interlayer debonding occurs, which causes deformation of the thermal insulation adhesive. Summary of the invention

[0004] The purpose of the present invention is to provide a modified polyamide particle and a preparation method and application thereof. The present invention generates zirconium oxide on glass fiber, and grafts more silane coupling agents in combination with a composite catalyst of tetramethylammonium hydroxide and ethylenediamine to increase the interface bonding force between a composite filler and polyamide. The surface of the composite filler is modified by syringaldehyde to increase the compatibility with a polyamide system. At the same time, the composite filler can react with anhydride in a styrene-maleic anhydride copolymer, which is beneficial to improving the mechanical strength of the modified polyamide particle.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] The modified polyamide particles comprise the following components by weight: 80-85 parts of polyamide resin, 15-20 parts of modified composite filler, 5-7 parts of compatibilizer, 0.5-1.0 parts of antioxidant and 0.3-0.5 parts of lubricant.

[0007] As a preferred technical solution of the present invention, the polyamide resin is one or more of PA6, PA66, PA610, PA612 and PA610.

[0008] As a preferred technical solution of the present invention, the compatibilizer is styrene-maleic anhydride copolymer;

[0009] As a preferred technical solution of the present invention, the antioxidant is one or more of antioxidant 1010, antioxidant 1098, antioxidant 168 and antioxidant 1076.

[0010] As a preferred technical solution of the present invention, the lubricant is pentaerythritol stearate.

[0011] The invention discloses a method for preparing the modified composite filler, which comprises the following steps:

[0012] Step 1: stir and disperse the chopped glass fibers, deionized water and ammonia water, preheat them, slowly add zirconium oxychloride and heat them, cool them to room temperature and filter them, wash the solids with water, and dry them in a vacuum oven to obtain a composite filler;

[0013] Step 2: placing the composite filler and ethanol in a reaction kettle, stirring and dispersing them, adding a catalyst and a silane coupling agent, heating and stirring, filtering to remove the filtrate, washing with alcohol, placing in an oven and vacuum drying to obtain a silane-modified filler;

[0014] Step 3: After the composite filler and ethanol are placed in a reaction kettle and stirred, aromatic aldehyde monomer is added, heated and stirred, centrifuged to remove the supernatant, washed with alcohol, and placed in an oven for vacuum drying to obtain a modified composite filler.

[0015] As a preferred technical solution of the present invention, in step one, the stirring and dispersing time is 30-45 minutes; the preheating is to raise the temperature to 50°C; the heat treatment is heated at 230-250°C for 6-8 hours; the water washing is to wash with deionized water until neutral; the vacuum drying is to dry at 120-130°C to constant weight.

[0016] As a preferred technical solution of the present invention, in step one, the usage ratio of the chopped glass fiber, deionized water, ammonia water and zirconium oxychloride is 9-10g:50-60mL:28-34mL:7.0-8.2g; the mass fraction of the ammonia water is 14-18%; the chopped glass fiber has a length of 3-5mm and a diameter of 10-14μm.

[0017] As a preferred technical solution of the present invention, in step 2, the stirring and dispersing is stirring at a speed of 500-600r / min for 30-40min; the heating stirring is stirring at a temperature of 60-75°C for 15-20min; the alcohol washing is washing with ethanol for 3 times; and the vacuum drying is drying at a temperature of 80-90°C to constant weight.

[0018] As a preferred technical solution of the present invention, in step 2, the mass ratio of the composite filler, ethanol, catalyst and silane coupling agent is 10-14:40-50:0.08-0.12:4.2-5.0; the silane coupling agent is silane coupling agent NQ-62; and the catalyst is a mixture of ethylenediamine and tetramethylammonium hydroxide in a mass ratio of 2.0-2.4:3.

[0019] As a preferred technical solution of the present invention, tetramethylammonium hydroxide is an organic base, in which the hydroxide ion (OH - ) can play a nucleophilic role and promote the hydrolysis reaction of the silane coupling agent.

[0020] As a preferred technical solution of the present invention, in the grafting reaction of the silane coupling agent, ethylenediamine can not only improve the dispersibility of the silane coupling agent in the reaction system, but also form a stable complex with the metal ions, which helps to regulate and control the hydrolysis and condensation reactions of the silane coupling agent, improve the reaction activity, and promote the chemical reaction of the silane coupling agent.

[0021] As a preferred technical solution of the present invention, in step three, the stirring and mixing time is 20-30 minutes; the heating and stirring is stirring at a temperature of 60-70°C for 4-6 hours; the alcohol washing is washing with anhydrous ethanol twice; and the vacuum drying is drying at a temperature of 80-90°C to constant weight.

[0022] As a preferred technical solution of the present invention, in step three, the mass ratio of the composite filler, ethanol and aromatic aldehyde monomer is 6-8:20-30:0.8-1.2; and the aromatic aldehyde monomer is syringaldehyde.

[0023] As a preferred technical solution of the present invention, the methoxy and hydroxyl groups on syringaldehyde can promote the grafting of syringaldehyde and amino groups through hydrogen bonding and electrostatic adsorption.

[0024] The present invention discloses a method for preparing the modified polyamide particles, comprising the following steps:

[0025] The polyamide resin, the compatibilizer, the antioxidant and the lubricant are mixed and kneaded, and then added into the twin-screw extruder from the main feeding port, and the modified composite filler is added from the side feeding, melt-extruded, cooled and pelletized to obtain modified polyamide particles.

[0026] As a preferred technical solution of the present invention, the melt extrusion temperature is 210-240°C.

[0027] As a preferred technical solution of the present invention, the modified polyamide particles are used in thermal insulation materials and sealing materials, specifically, the modified polyamide particles are used in thermal insulation strip materials and sealing strip materials.

[0028] Beneficial effects of the present invention:

[0029] The invention generates zirconium oxide on glass fiber, and grafts more silane coupling agents by combining tetramethylammonium hydroxide and ethylenediamine composite catalyst, thereby increasing the interface bonding force between the composite filler and the polyamide. The surface of the composite filler is modified by syringaldehyde to increase the compatibility with the polyamide system. At the same time, the composite filler can react with the anhydride in the styrene-maleic anhydride copolymer, thereby facilitating the improvement of the mechanical strength of the modified polyamide particles. DETAILED DESCRIPTION

[0030] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0031] Example 1

[0032] A modified polyamide particle comprises the following components by weight: 80 parts of polyamide resin, 15 parts of modified composite filler, 5 parts of compatibilizer, 0.5 parts of antioxidant and 0.3 parts of lubricant; the polyamide resin is PA6; the compatibilizer is styrene-maleic anhydride copolymer; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; the lubricant is pentaerythritol stearate;

[0033] Wherein, the preparation method of the modified composite filler comprises the following steps:

[0034] Step 1: stir and disperse the chopped glass fibers, deionized water and ammonia water, preheat them, slowly add zirconium oxychloride and heat them, cool them to room temperature and filter them, wash the solids with water, and dry them in a vacuum oven to obtain a composite filler;

[0035] Step 2: placing the composite filler and ethanol in a reaction kettle, stirring and dispersing them, adding a catalyst and a silane coupling agent, heating and stirring, filtering to remove the filtrate, washing with alcohol, placing in an oven and vacuum drying to obtain a silane-modified filler;

[0036] Step 3: After the composite filler and ethanol are placed in a reaction kettle and stirred, the aromatic aldehyde monomer is added and heated and stirred, the supernatant is removed by centrifugation, and then the mixture is washed with alcohol, and the mixture is placed in an oven and vacuum dried to obtain a modified composite filler;

[0037] In step 1, the stirring and dispersing time is 30 minutes; the preheating is to raise the temperature to 50°C; the heating treatment is to heat at 230°C for 6 hours; the water washing is to wash with deionized water until neutral; the vacuum drying is to dry at 120°C to constant weight;

[0038] In step 1, the ratio of the chopped glass fiber, deionized water, ammonia water and zirconium oxychloride is 9g:50mL:28mL:7.0g; the mass fraction of the ammonia water is 14%; the chopped glass fiber is 3mm in length and 10μm in diameter;

[0039] In step 2, the stirring and dispersing is stirring at a speed of 500 r / min for 30 minutes; the heating stirring is stirring at a temperature of 60° C. for 15 minutes; the alcohol washing is washing with ethanol for 3 times; and the vacuum drying is drying at a temperature of 80° C. to constant weight;

[0040] In step 2, the mass ratio of the composite filler, ethanol, catalyst and silane coupling agent is 10:40:0.08:4.2; the silane coupling agent is silane coupling agent NQ-62; the catalyst is a mixture of ethylenediamine and tetramethylammonium hydroxide in a mass ratio of 2.0:3;

[0041] In step three, the stirring and mixing time is 20 minutes; the heating and stirring is stirring at 60°C for 4 hours; the alcohol washing is washing with anhydrous ethanol twice; the vacuum drying is drying at 80°C to constant weight; in step three, the mass ratio of the composite filler, ethanol and aromatic aldehyde monomer is 6:20:0.8; the aromatic aldehyde monomer is syringaldehyde;

[0042] The preparation method of the modified polyamide particles comprises the following steps:

[0043] The polyamide resin, the compatibilizer, the antioxidant and the lubricant are mixed and kneaded, and then added into the twin-screw extruder from the main feeding port, and the modified composite filler is added from the side feeding, and then melt-extruded at 210° C., cooled and pelletized to obtain modified polyamide particles.

[0044] Example 2

[0045] A modified polyamide particle comprises the following components by weight: 81 parts of polyamide resin, 16 parts of modified composite filler, 5.5 parts of compatibilizer, 0.6 parts of antioxidant and 0.35 parts of lubricant; the polyamide resin is PA6; the compatibilizer is styrene-maleic anhydride copolymer; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; the lubricant is pentaerythritol stearate;

[0046] Wherein, the preparation method of the modified composite filler comprises the following steps:

[0047] Step 1: stir and disperse the chopped glass fibers, deionized water and ammonia water, preheat them, slowly add zirconium oxychloride and heat them, cool them to room temperature and filter them, wash the solids with water, and dry them in a vacuum oven to obtain a composite filler;

[0048] Step 2: placing the composite filler and ethanol in a reaction kettle, stirring and dispersing them, adding a catalyst and a silane coupling agent, heating and stirring, filtering to remove the filtrate, washing with alcohol, placing in an oven and vacuum drying to obtain a silane-modified filler;

[0049] Step 3: After the composite filler and ethanol are placed in a reaction kettle and stirred, the aromatic aldehyde monomer is added and heated and stirred, the supernatant is removed by centrifugation, and then the mixture is washed with alcohol, and the mixture is placed in an oven and vacuum dried to obtain a modified composite filler;

[0050] In step 1, the stirring and dispersing time is 34 minutes; the preheating is to raise the temperature to 50°C; the heating treatment is to heat at 235°C for 6.5 hours; the water washing is to wash with deionized water until neutral; the vacuum drying is to dry at 122°C to constant weight;

[0051] In step 1, the ratio of the chopped glass fiber, deionized water, ammonia water and zirconium oxychloride is 9.2g:52mL:30mL:7.3g; the mass fraction of the ammonia water is 15%; the chopped glass fiber is 4mm in length and 11μm in diameter;

[0052] In step 2, the stirring dispersion is stirring at a speed of 525 r / min for 32 minutes; the heating stirring is stirring at a temperature of 64° C. for 16 minutes; the alcohol washing is washing with ethanol for 3 times; and the vacuum drying is drying at a temperature of 82° C. to constant weight;

[0053] In step 2, the mass ratio of the composite filler, ethanol, catalyst and silane coupling agent is 11:42:0.09:4.4; the silane coupling agent is silane coupling agent NQ-62; the catalyst is a mixture of ethylenediamine and tetramethylammonium hydroxide in a mass ratio of 2.1:3;

[0054] In step 3, the stirring and mixing time is 22 minutes; the heating and stirring is stirring at 62°C for 4.5 hours; the alcohol washing is washing twice with anhydrous ethanol; the vacuum drying is drying at 82°C to constant weight; in step 3, the mass ratio of the composite filler, ethanol and aromatic aldehyde monomer is 6.5:22:0.9; the aromatic aldehyde monomer is syringaldehyde;

[0055] The preparation method of the modified polyamide particles comprises the following steps:

[0056] The polyamide resin, the compatibilizer, the antioxidant and the lubricant are mixed and kneaded, and then added into the twin-screw extruder from the main feeding port, and the modified composite filler is added from the side feeding, and then melt-extruded at 218° C., cooled and pelletized to obtain modified polyamide particles.

[0057] Example 3

[0058] A modified polyamide particle comprises the following components by weight: 82 parts of polyamide resin, 18 parts of modified composite filler, 6 parts of compatibilizer, 0.8 parts of antioxidant and 0.4 parts of lubricant; the polyamide resin is PA6; the compatibilizer is styrene-maleic anhydride copolymer; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; the lubricant is pentaerythritol stearate;

[0059] Wherein, the preparation method of the modified composite filler comprises the following steps:

[0060] Step 1: stir and disperse the chopped glass fibers, deionized water and ammonia water, preheat them, slowly add zirconium oxychloride and heat them, cool them to room temperature and filter them, wash the solids with water, and dry them in a vacuum oven to obtain a composite filler;

[0061] Step 2: placing the composite filler and ethanol in a reaction kettle, stirring and dispersing them, adding a catalyst and a silane coupling agent, heating and stirring, filtering to remove the filtrate, washing with alcohol, placing in an oven and vacuum drying to obtain a silane-modified filler;

[0062] Step 3: After the composite filler and ethanol are placed in a reaction kettle and stirred, the aromatic aldehyde monomer is added and heated and stirred, the supernatant is removed by centrifugation, and then the mixture is washed with alcohol, and the mixture is placed in an oven and vacuum dried to obtain a modified composite filler;

[0063] In step 1, the stirring and dispersing time is 38 minutes; the preheating is to raise the temperature to 50°C; the heating treatment is to heat at 240°C for 7 hours; the water washing is to wash with deionized water until neutral; the vacuum drying is to dry at 125°C to constant weight;

[0064] In step 1, the ratio of the chopped glass fiber, deionized water, ammonia water and zirconium oxychloride is 9.5 g: 55 mL: 31 mL: 7.6 g; the mass fraction of the ammonia water is 16%; the chopped glass fiber is 4 mm in length and 12 μm in diameter;

[0065] In step 2, the stirring dispersion is stirring at a speed of 550 r / min for 35 minutes; the heating stirring is stirring at a temperature of 68° C. for 18 minutes; the alcohol washing is washing with ethanol for 3 times; and the vacuum drying is drying at a temperature of 85° C. to constant weight;

[0066] In step 2, the mass ratio of the composite filler, ethanol, catalyst and silane coupling agent is 12:45:0.1:4.6; the silane coupling agent is silane coupling agent NQ-62; the catalyst is a mixture of ethylenediamine and tetramethylammonium hydroxide in a mass ratio of 2.2:3;

[0067] In step three, the stirring and mixing time is 25 minutes; the heating and stirring is stirring at a temperature of 65°C for 5 hours; the alcohol washing is washing with anhydrous ethanol twice; the vacuum drying is drying at a temperature of 85°C to constant weight; in step three, the mass ratio of the composite filler, ethanol and aromatic aldehyde monomer is 7:25:1; the aromatic aldehyde monomer is syringaldehyde;

[0068] The preparation method of the modified polyamide particles comprises the following steps:

[0069] The polyamide resin, the compatibilizer, the antioxidant and the lubricant are mixed and kneaded, and then added into the twin-screw extruder from the main feeding port, and the modified composite filler is added from the side feeding, and then melt-extruded at 225° C., cooled and pelletized to obtain modified polyamide particles.

[0070] Example 4

[0071] A modified polyamide particle comprises the following components by weight: 84 parts of polyamide resin, 19 parts of modified composite filler, 6.5 parts of compatibilizer, 0.9 parts of antioxidant and 0.45 parts of lubricant; the polyamide resin is PA6; the compatibilizer is styrene-maleic anhydride copolymer; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; the lubricant is pentaerythritol stearate;

[0072] Wherein, the preparation method of the modified composite filler comprises the following steps:

[0073] Step 1: stir and disperse the chopped glass fibers, deionized water and ammonia water, preheat them, slowly add zirconium oxychloride and heat them, cool them to room temperature and filter them, wash the solids with water, and dry them in a vacuum oven to obtain a composite filler;

[0074] Step 2: placing the composite filler and ethanol in a reaction kettle, stirring and dispersing them, adding a catalyst and a silane coupling agent, heating and stirring, filtering to remove the filtrate, washing with alcohol, placing in an oven and vacuum drying to obtain a silane-modified filler;

[0075] Step 3: After the composite filler and ethanol are placed in a reaction kettle and stirred, the aromatic aldehyde monomer is added and heated and stirred, the supernatant is removed by centrifugation, and then the mixture is washed with alcohol, and the mixture is placed in an oven and vacuum dried to obtain a modified composite filler;

[0076] In step 1, the stirring and dispersing time is 40 minutes; the preheating is to raise the temperature to 50°C; the heating treatment is to heat at 245°C for 7.5 hours; the water washing is to wash with deionized water until neutral; the vacuum drying is to dry at 128°C to constant weight;

[0077] In step 1, the ratio of the chopped glass fiber, deionized water, ammonia water and zirconium oxychloride is 9.8g:58mL:32mL:7.9g; the mass fraction of the ammonia water is 17%; the chopped glass fiber is 4mm in length and 13μm in diameter;

[0078] In step 2, the stirring dispersion is stirring at a speed of 570 r / min for 38 minutes; the heating stirring is stirring at a temperature of 71° C. for 19 minutes; the alcohol washing is washing with ethanol for 3 times; and the vacuum drying is drying at a temperature of 88° C. to constant weight;

[0079] In step 2, the mass ratio of the composite filler, ethanol, catalyst and silane coupling agent is 13:48:0.11:4.8; the silane coupling agent is silane coupling agent NQ-62; the catalyst is a mixture of ethylenediamine and tetramethylammonium hydroxide in a mass ratio of 2.3:3;

[0080] In step 3, the stirring and mixing time is 28 minutes; the heating and stirring is stirring at 68°C for 5.5 hours; the alcohol washing is washing twice with anhydrous ethanol; the vacuum drying is drying at 88°C to constant weight; in step 3, the mass ratio of the composite filler, ethanol and aromatic aldehyde monomer is 7.5:28:1.1; the aromatic aldehyde monomer is syringaldehyde;

[0081] The preparation method of the modified polyamide particles comprises the following steps:

[0082] The polyamide resin, the compatibilizer, the antioxidant and the lubricant are mixed and kneaded, and then added into a twin-screw extruder from a main feed port, and the modified composite filler is added from a side feed, and the mixture is melt-extruded at 235° C., cooled, and pelletized to obtain modified polyamide particles.

[0083] Example 5

[0084] A modified polyamide particle comprises the following components by weight: 85 parts of polyamide resin, 20 parts of modified composite filler, 7 parts of compatibilizer, 1.0 part of antioxidant and 0.5 part of lubricant; the polyamide resin is PA6; the compatibilizer is styrene-maleic anhydride copolymer; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; the lubricant is pentaerythritol stearate;

[0085] Wherein, the preparation method of the modified composite filler comprises the following steps:

[0086] Step 1: stir and disperse the chopped glass fibers, deionized water and ammonia water, preheat them, slowly add zirconium oxychloride and heat them, cool them to room temperature and filter them, wash the solids with water, and dry them in a vacuum oven to obtain a composite filler;

[0087] Step 2: placing the composite filler and ethanol in a reaction kettle, stirring and dispersing them, adding a catalyst and a silane coupling agent, heating and stirring, filtering to remove the filtrate, washing with alcohol, placing in an oven and vacuum drying to obtain a silane-modified filler;

[0088] Step 3: After the composite filler and ethanol are placed in a reaction kettle and stirred, the aromatic aldehyde monomer is added and heated and stirred, the supernatant is removed by centrifugation, and then the mixture is washed with alcohol, and the mixture is placed in an oven and vacuum dried to obtain a modified composite filler;

[0089] In step 1, the stirring and dispersing time is 45 minutes; the preheating is to raise the temperature to 50°C; the heating treatment is to heat at 250°C for 8 hours; the water washing is to wash with deionized water until neutral; the vacuum drying is to dry at 130°C to constant weight;

[0090] In step 1, the ratio of the chopped glass fiber, deionized water, ammonia water and zirconium oxychloride is 10g:60mL:34mL:8.2g; the mass fraction of the ammonia water is 18%; the chopped glass fiber is 5mm in length and 14μm in diameter;

[0091] In step 2, the stirring and dispersing is stirring at a speed of 600 r / min for 40 minutes; the heating stirring is stirring at a temperature of 75° C. for 20 minutes; the alcohol washing is washing with ethanol for 3 times; and the vacuum drying is drying at a temperature of 90° C. to constant weight;

[0092] In step 2, the mass ratio of the composite filler, ethanol, catalyst and silane coupling agent is 14:50:0.12:5.0; the silane coupling agent is silane coupling agent NQ-62; the catalyst is a mixture of ethylenediamine and tetramethylammonium hydroxide in a mass ratio of 2.4:3;

[0093] In step three, the stirring and mixing time is 30 minutes; the heating and stirring is stirring at 70°C for 6 hours; the alcohol washing is washing twice with anhydrous ethanol; the vacuum drying is drying at 90°C to constant weight; in step three, the mass ratio of the composite filler, ethanol and aromatic aldehyde monomer is 8:30:1.2; the aromatic aldehyde monomer is syringaldehyde;

[0094] The preparation method of the modified polyamide particles comprises the following steps:

[0095] The polyamide resin, the compatibilizer, the antioxidant and the lubricant are mixed and kneaded, and then added into the twin-screw extruder from the main feeding port, and the modified composite filler is added from the side feeding, and the modified polyamide particles are obtained by melt extrusion at 240°C, cooling and pelletizing.

[0096] Comparative Example 1-2

[0097] Compared with Example 3, the difference between Comparative Example 1-2 is that the amount of catalyst used is as shown in Table 1; the other components, preparation steps and parameters are the same.

[0098] Table 1

[0099] Ethylenediamine (parts by weight) Tetramethylammonium hydroxide (parts by weight) Example 3 2.2 3 Comparative Example 1 0 5.2 Comparative Example 2 5.2 0

[0100] Comparative Example 3

[0101] Compared with Example 3, Comparative Example 3 is different in that zirconium oxychloride is not used, and the other components, preparation steps and parameters are the same.

[0102] Comparative Example 4

[0103] Compared with Example 3, Comparative Example 4 is different in that after mixing zirconium oxide and chopped glass fibers, composite particles are obtained to replace the composite filler, and the other components, preparation steps and parameters are the same.

[0104] Comparative Example 5

[0105] Compared with Example 3, the difference in Comparative Example 5 is that the silane coupling agent in step 2 is silane coupling agent KH-550, and the other components, preparation steps and parameters are the same.

[0106] Comparative Example 6

[0107] Compared with Example 3, Comparative Example 6 is different in that no aromatic aldehyde monomer is used, and the remaining components, preparation steps and parameters are the same.

[0108] Comparative Example 7

[0109] Compared with Example 3, Comparative Example 7 is different in that no compatibilizer is used, and the remaining components, preparation steps and parameters are the same.

[0110] The modified polyamide particles obtained in Examples 1-5 and Comparative Examples 1-7 were subjected to the following mechanical property tests, and the test results are shown in Table 2;

[0111] Mechanical properties test:

[0112] Test tensile strength and elongation at break according to ISO-527-2;

[0113] The notched impact strength of the simply supported beam was tested according to ISO-179-1.

[0114] Table 2

[0115] Tensile strength(MPa) Elongation at break (%) <![CDATA[Impact strength (KJ / m 2 )]]> Example 1 123 3.78 11.5 Example 2 125 3.81 11.6 Example 3 129 3.88 11.8 Example 4 126 3.83 11.6 Example 5 121 3.75 11.3 Comparative Example 1 105 2.17 7.9 Comparative Example 2 103 2.13 7.7 Comparative Example 3 94 1.58 7.1 Comparative Example 4 97 1.71 7.3 Comparative Example 5 91 1.19 6.7 Comparative Example 6 112 2.63 8.3 Comparative Example 7 99 1.91 7.5

[0116] From the test results in Table 2, it can be seen that compared with Comparative Examples 1-7, the modified polyamide particles prepared in Examples 1-5 of the present invention have excellent mechanical properties, which are better than the modified polyamide particles prepared in Comparative Examples 1-7.

[0117] The present invention places glass fiber in an environment of ammonia water and zirconium ions, generates zirconium oxide on the glass fiber through a hydrothermal reaction, increases the specific surface area and pore structure of the composite filler, grafts more silane coupling agents in combination with a composite catalyst, introduces amino groups and unsaturated carbon-carbon double bonds, and the carbon-carbon double bonds can form chemical bonds with polyamide to increase the interface bonding force between the composite filler and the polyamide, modifies the surface of the composite filler through a small amount of syringaldehyde to form an imine chemical bond with a self-repairing function, increases the compatibility with the polyamide system, and simultaneously makes the modified composite filler contain amino groups and benzene ring structures, which can react with the anhydride in the styrene-maleic anhydride copolymer, and improves the compatibility of the styrene-maleic anhydride copolymer and the modified composite filler through the amino groups and the benzene ring structures, which is beneficial to improve the mechanical strength of the modified polyamide particles.

[0118] The present invention uses tetramethylammonium hydroxide and ethylenediamine as a catalyst, and promotes the hydrolysis and condensation reactions of the silane coupling agent through nucleophilic catalysis, coordination and improved dispersibility, thereby promoting the chemical bonding of the silane coupling agent and the composite filler, enhancing the dispersion state of the inorganic filler in the polymer matrix, and improving the mechanical properties of the material.

[0119] The acid anhydride in the styrene-maleic anhydride copolymer of the present invention is polymerized in situ with the amine group in the polyamide to generate a graft copolymer containing both styrene structural segments and polyamide segments, and the modified composite filler also contains a benzene ring structure, thereby significantly increasing the compatibility of the modified composite filler and the styrene-maleic anhydride copolymer in the polyamide, which is beneficial to improving the mechanical properties of the final polyamide material. At the same time, the acid anhydride in the styrene-maleic anhydride copolymer can also react with the amino group of the modified composite filler, which is beneficial to improving the compatibility of the styrene-maleic anhydride copolymer and the modified composite filler, and further improving the flexibility and strength of the modified polyamide particles.

[0120] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A modified polyamide particle, characterized in that: The composition comprises the following components by weight: 80-85 parts of polyamide resin, 15-20 parts of modified composite filler, 5-7 parts of compatibilizer, 0.5-1.0 parts of antioxidant and 0.3-0.5 parts of lubricant; the compatibilizer is styrene-maleic anhydride copolymer; The preparation method of the modified composite filler comprises the following steps: Step 1: Stir and disperse the chopped glass fiber, deionized water and ammonia water, preheat them, slowly add zirconium oxychloride and heat them, cool them to room temperature and filter them, wash the solids with water, and dry them in an oven under vacuum to obtain a composite filler; the amount ratio of the chopped glass fiber, deionized water, ammonia water and zirconium oxychloride is 9-10g:50-60mL:28-34mL:7.0-8.2g; Step 2: After the composite filler and ethanol are placed in a reaction kettle and stirred and dispersed, a catalyst and a silane coupling agent are added, the mixture is heated and stirred, the filtrate is filtered out and then washed with alcohol, and the mixture is placed in an oven and vacuum dried to obtain a silane-modified filler; the mass ratio of the composite filler, ethanol, catalyst and silane coupling agent is 10-14:40-50:0.08-0.12:4.2-5.0; the silane coupling agent is silane coupling agent NQ-62; the catalyst is prepared by mixing ethylenediamine and tetramethylammonium hydroxide in a mass ratio of 2.0-2.4:3; Step 3: Place the composite filler and ethanol in a reaction kettle and stir to mix, then add aromatic aldehyde monomer, heat and stir, centrifuge to remove the supernatant, wash with alcohol, place in an oven and vacuum dry to obtain a modified composite filler; the mass ratio of the composite filler, ethanol and aromatic aldehyde monomer is 6-8:20-30:0.8-1.2; the aromatic aldehyde monomer is syringaldehyde.

2. The modified polyamide particles according to claim 1, characterized in that: The polyamide resin is one or more of PA6, PA66, PA610, PA612 and PA610; the antioxidant is one or more of antioxidant 1010, antioxidant 1098, antioxidant 168 and antioxidant 1076; and the lubricant is pentaerythritol stearate.

3. The modified polyamide particles according to claim 1, characterized in that: In step 1, the stirring and dispersing time is 30-45 minutes; the preheating is to raise the temperature to 50° C.; the water washing is to use deionized water to wash to neutrality; and the vacuum drying is to dry at a temperature of 120-130° C. to constant weight.

4. The modified polyamide particles according to claim 1, characterized in that: In step 1, the mass fraction of the ammonia water is 14-18%; the chopped glass fibers are 3-5 mm in length and 10-14 μm in diameter.

5. The modified polyamide particles according to claim 1, characterized in that: In step one, the heating treatment is performed at 230-250° C. for 6-8 hours.

6. The modified polyamide particles according to claim 1, characterized in that: In step 2, the stirring and dispersing is stirring at a speed of 500-600 r / min for 30-40 minutes; the heating stirring is stirring at a temperature of 60-75°C for 15-20 minutes; the alcohol washing is washing with ethanol for 3 times; and the vacuum drying is drying at a temperature of 80-90°C to constant weight.

7. The modified polyamide particles according to claim 1, characterized in that: In step three, the stirring and mixing time is 20-30 minutes; the heating and stirring is stirring at a temperature of 60-70°C for 4-6 hours; the alcohol washing is washing with anhydrous ethanol twice; and the vacuum drying is drying at a temperature of 80-90°C to constant weight.

8. A method for preparing modified polyamide particles according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: mixing polyamide resin, a compatibilizer, an antioxidant and a lubricant, adding them into a twin-screw extruder from a main feeding port, adding a modified composite filler from a side feeding port, melting and extruding, cooling and pelletizing to obtain modified polyamide particles.

9. The method for preparing modified polyamide particles according to claim 8, characterized in that: The melt extrusion temperature is 210-240°C.

10. Use of the modified polyamide particles according to any one of claims 1 to 7, characterized in that: Application of the modified polyamide particles in thermal insulation materials and sealing materials.

Citation Information

Patent Citations

  • Heat-resistant polyamide reinforced material with low water absorption rate and preparation method thereof

    CN109929243A

Cited By

  • Multifunctional composite foaming agent for PVC soles and preparation method thereof

    CN120271881A

  • High-strength wear-resistant polyamide material and preparation method thereof

    CN120442038A